Diabelskie koło historii. Poetyki miejskie w powieści Aleksieja Iwanowa Cienie Teutonów - Pavlenko, Svetlana (Studia Rossica Posnaniensia, 2024)
Shadows of the Teutons, a novel by the contemporary Russian writer Aleksei Ivanov, was published in 2021. The story unfolds across two different time periods. Some events take place in 1457 during the siege of Marienburg, the capital of the Teutonic Order’s State, and the Polish-Teutonic conflict serves as a starting point for the depiction of later battles, in 1945, within the former East Prussia, now known as the Kaliningrad Oblast. This article examines the means used to create the urban spaces depicted in the novel and their transformation as a result of armed conflicts. It focuses on the urban landscapes of Baltiysk (Pillau) and Malbork (Marienburg), which exhibit a complex identity and strong interconnections at various levels of the narrative structure. The analysis explores somatopoetics and thanatopoetics, two categories the author employs to describe places, as well as the auditory and olfactory dimensions of everyday wartime experiences, memoryscapes, Teutonic castles and underground settings such as cellars, bunkers, catacombs, secret passages and tunnels.